2021
DOI: 10.1111/ddi.13228
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale eDNA metabarcoding survey reveals marine biogeographic break and transitions over tropical north‐western Australia

Abstract: Aim Environmental DNA (eDNA) metabarcoding has demonstrated its applicability as a highly sensitive biomonitoring tool across small spatial and temporal scales in marine ecosystems. However, it has rarely been tested across large spatial scales or biogeographical barriers. Here, we scale up marine eDNA metabarcoding, test its ability to detect a major marine biogeographic break and evaluate its use as a regional biomonitoring tool in Australia. Location North‐western Australia (NWA). Methods We applied metabar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 73 publications
3
54
1
Order By: Relevance
“…However, the performance of eDNA metabarcoding in comparative studies has brought inconclusive results, particularly in terms of its detection scale and in the number of detected and undetected species; e.g., studies in coastal habitats have suggested scales going from dozen meters (Jeunen et al, 2019;Port et al, 2016) to a few kilometers (O'Donnell et al, 2017). Detection scale is a relevant aspect because it determines the type of process that can be studied, from local reef dynamics within different habitats (Lafferty et al, 2020;West et al, 2020) to broader diversity gradients (Closek et al, 2019) and potentially even larger biogeographic patterns (West et al, 2021). In marine metabarcoding studies local oceanographic features influence this detection scale (Hansen et al, 2018;Thomsen et al, 2012) and can lead to larger diversity estimates than those captured by established monitoring approaches (Calderón-Sanou et al, 2019), because of the transport of the molecules from distant sources.…”
mentioning
confidence: 99%
“…However, the performance of eDNA metabarcoding in comparative studies has brought inconclusive results, particularly in terms of its detection scale and in the number of detected and undetected species; e.g., studies in coastal habitats have suggested scales going from dozen meters (Jeunen et al, 2019;Port et al, 2016) to a few kilometers (O'Donnell et al, 2017). Detection scale is a relevant aspect because it determines the type of process that can be studied, from local reef dynamics within different habitats (Lafferty et al, 2020;West et al, 2020) to broader diversity gradients (Closek et al, 2019) and potentially even larger biogeographic patterns (West et al, 2021). In marine metabarcoding studies local oceanographic features influence this detection scale (Hansen et al, 2018;Thomsen et al, 2012) and can lead to larger diversity estimates than those captured by established monitoring approaches (Calderón-Sanou et al, 2019), because of the transport of the molecules from distant sources.…”
mentioning
confidence: 99%
“…Vertebrate primers are particularly susceptible to off-target microbial amplification that can overwhelm the signature of the targeted vertebrate groups. Removal of these microbial products before sequencing is required to enhance the quality of vertebrate assays (West et al, 2021). b) shows the relationship between phytoplankton biomass estimated from microscopic counts and eDNA reads for diatoms; both follow an expected pattern similar to chlorophyll, given that diatoms are the primary bloom formers under upwelling conditions (Chavez et al, 2017).…”
Section: The General Distribution Of Edna Concentration In the Marine Environmentmentioning
confidence: 99%
“…In north‐western Australia, West et al. (2021) applied metabarcoding of the mitochondrial 16S rRNA and CO1 genes to detect bony fish, elasmobranchs and aquatic reptiles from 71 mid‐shelf, inshore, coastal and nearshore estuarine sites. Their eDNA metabarcoding was a highly sensitive detection tool that was able to discern fine‐scale patterns of marine fishes across the large‐scale oceanic region.…”
Section: This Issuementioning
confidence: 99%